Evaluation of the services offered by the Family Health Strategy (ESF) in a municipality in southern Brazil (Research, Society and Development, 2021)
This study aimed to evaluate the services offered in a Family Health Strategy (FHS) in the city of Santo Ângelo (RS). For this, an observational research was carried out between October 2019 and March 2020, by the members of the Education through Work for Health Program (PET-Saúde-Interprofessionality), with 156 participants. Attributes were assessed using the Primary Care Assessment instrument adapted to the local reality (adapted PCA-Tool). Among the interviewees, the attributes that showed positive relevance were degree of affiliation, with 87.6% of the participants looking for FHS in their neighborhood. The longitudinality, with a score of 8.9, coordination-information system with a score of 9.3, integration of care with a score of 8.8 and services available in the unit with 8.2, were the best rated items. The low results were: accessibility with a score of 6.9, services provided and community guidance, both with average scores 5.7. The overall score for the evaluation of all attributes was 7.7. It was evidenced that the FHS performs well in several analyzed attributes. However, with regard to community orientation, integrality and services provided, it has some flaws, highlighting the need for a change in strategies, focusing more on guidelines aimed at the family and community.